Perancangan Aplikasi Penerimaan Dan Pengeluaran Di TPQ-TQA Masjid Raya Andalas Dengan Menggunakan Microsoft Access 2021 - Wardani, Anggun Fatresia; Handayani, Desi; Sriyunianti, Fera (Jurnal Ilmiah Raflesia Akuntansi, 2024)
This research aims to design an income and expenditure application for TPQ-TQA Masjid Raya Andalas using Microsoft Access software. The research findings revealed deficiencies in financial recording and reporting. To address these issues, the author proposes a solution through the development of an application designed to assist in recording transactions and generating financial reports in accordance with Financial Accounting Standards (SAK) quickly and automatically. The application is tailored to the specific needs and is equipped with forms utilizing Visual Basic for Applications (VBA) and a login feature to enhance application security. The forms include an account registry form, fixed asset registry form, student data form, teacher data form, class registry form, invoice form, overdue student payment receipt form, remaining student payment form, donation receipt form, general journal form, cash expenditure form, and fixed asset depreciation form. The application also presents financial reports such as the balance sheet, cash flow statement, comprehensive income statement, statement of changes in net assets, and other relevant data for TPQ-TQA.